Enhancing Social Studies Outcomes Through Experiential Learning and Social-Emotional Development Using Poster Media in Fifth-Grade Classrooms - Muhamad Rusadi Letasado; Julhidayat Muhsam; I Wayan Lasmawan (STAI Hubbulwathan Duri, 2024)
This study evaluates the impact of an experiential learning model, supported by poster media, on social studies learning outcomes among fifth-grade students at SD Negeri 1 Sikumana, Kupang City. Social and Emotional Learning (SEL) plays a critical role in primary education, fostering academic and social growth, promoting positive behavior, and creating an inclusive learning environment. A quasi-experimental design with a post-test-only control group was employed. The population consisted of 60 students, with 30 students randomly sampled to ensure equal selection probability. Social studies learning outcomes were assessed through a multiple-choice test, and data were analyzed using descriptive statistics and one-way ANOVA. The analysis revealed a significant effect of the experiential learning model on social studies learning outcomes (F(1, 28) = 19.551, p 0.05). The results indicate that the experiential learning approach, coupled with poster media, meaningfully enhances learning outcomes, with the F value exceeding the F table value and a significance level below 0.05. This led to the rejection of the null hypothesis (Ho) and the acceptance of the alternative hypothesis (H1). The findings suggest that adopting experiential learning models tailored to students' needs can improve engagement and academic performance. Teachers are encouraged to use evidence-based methods that accommodate diverse learning styles, fostering better outcomes. This study highlights the effectiveness of experiential learning enhanced by poster media in improving social studies outcomes, providing a foundation for refining teaching practices and informing educational policies to support student success and well-being.